PO 88 - CONTINUOUS ERECTOR SPINAE BLOCK FOR RIB FRACTURE - A CASE-REPORT - Veiga, Joana; Almeida, Paulo; Silva, Rafaela; Ferreira, Carmélia; Ribeiro, Lara (Revista da Sociedade Portuguesa de Anestesiologia, 2023)
x